Kedudukan Asas Proporsionalitas dalam Perjanjian Timbal Balik Abstrak - Faradilla Meisya Valda (Pemuliaan Keadilan, 2025)
The principle of proportionality plays an important role in ensuring the balance of rights and obligations between the parties in a reciprocal agreement. In the context of Indonesian contract law, this principle functions as a mechanism to prevent inequality that can harm one of the parties, especially in commercial and complex contracts. As stated by Hernoko (2016), the application of the principle of proportionality in commercial contracts aims to create substantive justice through a balanced exchange of rights and obligations between the parties. This study uses a normative legal approach with a literature study method, which involves an analysis of related laws and regulations and case studies. This approach allows researchers to explore the application of the principle of proportionality in various types of reciprocal agreements, including franchise agreements and construction service contracts. For example, a study by Susanto et al. (2021)1 highlights how the principle of proportionality is applied in construction service contracts to ensure a fair distribution of responsibilities between contractors and clients. The results of the analysis show that consistent application of the principle of proportionality can improve justice in contractual relationships. In franchise agreements, for example, Rahmawan et al. (2020)2 found that the application of this principle helps create a balance between the rights and obligations of franchisors and franchisees, who often have different bargaining positions. Thus, the principle of proportionality functions not only as a legal principle, but also as a practical tool to achieve justice in contractual practices.